Answer:
Divide both sides by a constant to simplify the equation. Thus the second option.
Explanation:
Solve for x:
9 - 10 x = -1
Hint: | Isolate terms with x to the left hand side.
Subtract 9 from both sides:
(9 - 9) - 10 x = -9 - 1
Hint: | Look for the difference of two identical terms.
9 - 9 = 0:
-10 x = -9 - 1
Hint: | Evaluate -9 - 1.
-9 - 1 = -10:
-10 x = -10
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of -10 x = -10 by -10:
(-10 x)/(-10) = (-10)/(-10)
Hint: | Any nonzero number divided by itself is one.
(-10)/(-10) = 1:
x = (-10)/(-10)
Hint: | Any nonzero number divided by itself is one.
(-10)/(-10) = 1:
Answer: x = 1